Chiroptical properties of anionic and neutral nickel(II) bis(dithiolene) complexes based on methyl and dimethyl‐dddt ligands. Issue 1 (23rd October 2021) - Abhervé, Alexandre; Mroweh, Nabil; Cauchy, Thomas; Pop, Flavia; Vanthuyne, Nicolas; Avarvari, Narcis
Abstract: Racemic and enantiopure nickel(II) bis(dithiolene) anionic and neutral complexes based on the methyl‐5, 6‐dihydro‐1, 4‐dithiin‐2, 3‐dithiolate (me‐dddt) and dimethyl‐5, 6‐dihydro‐1, 4‐dithiin‐2, 3‐dithiolate (dm‐dddt) ligands have been experimentally and theoretically investigated with a special focus on their chiroptical properties. According to the time‐dependent density‐functional theory (TD‐DFT) calculations, the strong near‐infrared absorption bands typical for such complexes are only weakly active in circular dichroism (CD), and moreover, they have opposite signs for the axial and equatorial conformations, due to the variation of the angle between the transition electric and magnetic dipole moments, thus leading to the mutual cancellation of their contributions and the absence of these bands in the experimental CD spectra. The influence of the number of stereogenic centers and of the oxidation state of the complexes on their chiroptical properties is highlighted. The solid‐state structure of the complex (TMA)[Ni( rac ‐me‐dddt)2 ] (TMA = tetramethylammonium), determined by single‐crystal X‐ray diffraction analysis, shows a rather unusual cis arrangement of the two dithiolene ligands, with the methyl substituents adopting an axial conformation, which is not the most stable one in the gas phase. Abstract :